2008
DOI: 10.1097/shk.0b013e31815abbc6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Free Fatty Acid Levels in Septic Patients Are Associated With Cardiac Damage and Reduction in Heart Rate Variability

Abstract: Introduction Many authors have written about the need to treat patients closer to their beds, in order to observe them more as distinct people. The FAST HUG mnemonic, which consists of a checklist, was suggested as an idea to be employed everyday, by professionals dealing with patients who are critically ill. Minding these questions and motivated by an idea of follow patients' treatment closer, we have put into practice the instrument developed by Jean-Louis Vincent, evaluating the seven most important procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…Sepsis is associated with altered lipoprotein metabolism characterized by elevated plasma triglyceride and free fatty acid levels [21, 99–101] and suppression of energy production in several organs, including the heart [20, 21, 22•] (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis is associated with altered lipoprotein metabolism characterized by elevated plasma triglyceride and free fatty acid levels [21, 99–101] and suppression of energy production in several organs, including the heart [20, 21, 22•] (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…In studies of patients with sepsis or septic shock, our group has previously demonstrated that, on the first and sixth day of sepsis, nonsurvivors present higher serum levels of FFAs than do survivors [19,34]. We have also shown that FFA levels are elevated in patients with cardiac mitochondrial damage and changes in heart rate variability [19,34], as well as that oxidative stress activates poly(adenosine diphosphate-ribose) polymerase in the hearts of nonsurvivors of sepsis [34].…”
Section: Discussionmentioning
confidence: 93%
“…To detect a 20% reduction in FFA and oxLDL levels [19], with a 5% level of significance (two-tailed) and a power of 80%, the required sample size (given an anticipated dropout rate of 10%) was 24 patients per group.…”
Section: Study Site and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…As a corollary, patients with high levels of plasma OA have a higher risk of developing ARDS [19] or showing deleterious effects on their heart muscle [40]. Therefore, we can suggest that lowering OA plasma levels could help in the prevention of the high mortality and morbidity of ARDS.…”
Section: Discussionmentioning
confidence: 99%